Studi tentang kualitas layanan digital I-BAGENDIT dan hubungannya dengan citra Dinas Perpustakaan dan Kearsipan Kabupaten Garut Provinsi Jawa Barat: Studi eksplanatori survey - Yunus Winoto; Sukaesih Sukaesih (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2020)
This study aims to determine the quality of i-bagendit digital services with the image of the Library and Archives Office of Garut Regency, West Java Province. The variables of digital service quality include aspects of reliability, responsiveness, assurance, empathy and aspects of physical products. As for the dependent variable, namely about image. For the theoretical basis using Anthony Giddens' structuration theory which formulates the production and reproduction of members of the social system as resources in interaction. The approach used in this study uses a quantitative approach with a survey explanatory research type. The population in this study were members of the i-bagendit digital library with the sampling technique using simple random sampling (simple random sampling). For data collection techniques are carried out through interview questionnaires and through literature study. Based on the results of the study, it is known that the results of the sub-variable testing of reliability, responsiveness, assurance, empathy and physical products with the image of the Office of Library and Archives of West Java Province show a significant or significant relationship. So in general conclusions from this study illustrates that the quality of i-bagendit digital services is related to the image of the Garur Regency Library and Archives Office, West Java Province, meaning that the quality of i-Bagendit digital services with aspects of reliability, responsiveness, assurance, empathy and products Physical response by library users is positive, it will form a positive image of the library institution.